Phytase Supplementation to Corn Germ Meal Based Low Phosphorus Diets: Growth Performance and Phosphorus Retention in Coloured Broilers - Sowjanya Lakshmi, R. Kasi; Gloridoss, R.G.; Singh, K. Chandrapal (Indian Journal of Animal Nutrition, 2018)
A study was conducted with colored (Raja-II) broilers (1-42 d of age) fed corn germ meal (CGM) based low phosphorus diets supplemented with phytase enzyme to evaluate growth performance, phosphorus retention and tibia ash content. A total of 150 day old colored broiler chicks were allotted to five treatments of 30 birds in each (five replicates of six birds each). The control diet containing P at optimum level without phytase and CGM served as control. Experimental diets were prepared by replacing dicalcium phosphate in control diet with lime stone powder and by supplementing phytase enzyme (2500 IU). The diets were further prepared by incorporating CGM at 15, 20 and 25% to the diet supplemented with phytase (2500 IU). There was significant (P<0.05) difference in body weight gain (BWG) of control (1369) with 0% CGM fed groups without DCP (1202) group but non-significant with other treatment groups. Feed intake and FCR values were similar in all the treatments. Addition of phytase enzyme improved (P<0.05) tibia ash percentage in CGM fed groups and P retention percentage showed decrease (P<0.05) in CGM fed groups in comparison to control group in spite of phytase supplementation. Hence, CGM could be included in diets of colored broilers up to 25% level keeping P at low level and by supplementing phytase enzyme without affecting bird’s performance.